L’essor de la résilience ou la promotion de nouvelles cultures du risque autour de l’adaptation aux changements climatiques ? - Florence Rudolf (Développement Durable et Territoires)
The rising of adaptation policies, connected to the buzzword resiliency, does it modify the understanding of risk issues as it has been developed in the continuity of the analysis of risk society, proposed by Beck and Giddens? Following these authors, risk issues are the consequences of the control obsession of the Moderns. Therefore, the emancipation of this imaginary, through the increasing of reflexivity, appeared as the first step for a risk policy. How far does the rising of resilience sign a return to an ideology of control or a temptation for new principles of action ? How far does the enthusiasm for resilience correspond to a backlash in comparison to the late modernity or not ? This question was in the core of the communications about the framing of urban spaces and buildings to face climate changes, which have taken place at the congress of Acfas in may 2014 at the University of Concordia in Montreal.